Dietary antioxidants protect gut epithelial cells from oxidant-induced apoptosis - Bobrowski Paul; Reuter Brian K; Angeles Fausto M; Miller Mark JS; Sandoval Manuel (BMC, 2001)
Abstract Background The potential of ascorbic acid and two botanical decoctions, green tea and cat's claw, to limit cell death in response to oxidants were evaluated in vitro. Methods Cultured human gastric epithelial cells (AGS) or murine small intestinal epithelial cells (IEC-18) were exposed to oxidants - DPPH (3 μM), H2O2 (50 μM), peroxynitrite (300 μM) - followed by incubation for 24 hours, with antioxidants (10 μg/ml) administered as a 1 hour pretreatment. Cell number (MTT assay) and death via apoptosis or necrosis (ELISA, LDH release) was determined. The direct interactions between antioxidants and DPPH (100 μM) or H2O2 (50 μM) were evaluated by spectroscopy. Results The decoctions did not interact with H2O2, but quenched DPPH although less effectively than vitamin C. In contrast, vitamin C was significantly less effective in protecting human gastric epithelial cells (AGS) from apoptosis induced by DPPH, peroxynitrite and H2O2 (P < 0.001). Green tea and cat's claw were equally protective against peroxynitrite and H2O2, but green tea was more effective than cat's claw in reducing DPPH-induced apoptosis (P < 0.01). Necrotic cell death was marginally evident at these low concentrations of peroxynitrite and H2O2, and was attenuated both by cat's claw and green tea (P < 0.01). In IEC-18 cells, all antioxidants were equally effective as anti-apoptotic agents. Conclusions These results indicate that dietary antioxidants can limit epithelial cell death in response to oxidant stress. In the case of green tea and cat's claw, the cytoprotective response exceed their inherent ability to interact with the injurious oxidant, suggestive of actions on intracellular pathways regulating cell death.